Probiotics fermentation enhanced the bioactive properties of Gnaphalium affine water extract and improved regulation ability of gut microbiota - Qin Zhang; Shiying Yan; YuanYuan Luo; Zixin Meng; Zhihao Yu; Jian Zhao; Xiaojuan Wu; Yiming Tian; Guzhen Cui; Zhenghong Chen; Daoyan Wu (Food Chemistry: X)
This study investigated the probiotic potential of fermented beverages derived from Gnaphalium affine (G. affine). Three different beverages were prepared by fermenting G. affine water extract with Limosilactobacillus fermentum A6-3 (L. fermentum A6-3), Lactobacillus reuteri A27-1 (L. reuteri A27-1), or both for 48 h. The results demonstrated that bioactive compounds from G. affine promoted the growth of these two probiotics and preserved their viability for at least 28 days at 4 °C. Following fermentation, the concentrations of chlorogenic acid, coniferin, lactic acid, glycolic acid, and behenic acid were significantly elevated. Additionally, the G. affine fermented beverages promoted the growth of intestinal probiotics such as Lactobacillus, Bifidobacterium, while inhibiting pathogens like Clostridium, Shigella. Moreover, the G. affine fermented beverages exhibited beneficial effects, including antibacterial, antioxidant, anti-inflammatory activities. In conclusion, G. affine preserved the viability of probiotics, and probiotic, in turn, enhanced the beneficial functions of the G. affine fermented beverages.